Electric submersible pump vibration analysis under several operational conditions for vibration fault differential diagnosis. (1st January 2021) - Reges, Galdir; Fontana, Marcio; Ribeiro, Marcos; Silva, Tiago; Abreu, Odilon; Reis, Ricardo; Schnitman, Leizer
Abstract: An Electric Submersible Pump (ESP) vibration analysis was performed, considering different wear states and operational conditions. The pumps were tested with different fluid viscosities, operating points, and speeds to evaluate their vibration behavior, with the aim of providing characteristics for non-invasive differential vibration diagnosis. A specific frequency spectrum estimation method is described, focusing on the extraction of frequency component vibration amplitudes used in the petroleum industry-standard vibration analysis. A time-interval definition procedure was proposed to reduce signal amplitude losses due to variation of synchronous operating frequency. The results indicate that the frequency component peak amplitudes can be more accurately identified during synchronous frequency variation by the proposed method than by typical estimation methods. In this study, an ESP vibration differential diagnosis was achieved by analyzing relations between orders of the synchronous frequency, and by distinguishing that the synchronous component amplitude rose approximately proportionally to the square of the rotating speed; this differentiates unbalance fault from a bent shaft or a misalignment. A correlation matrix analysis is provided to demonstrate that variation in the fluid-temperature difference between the pump intake and discharge is related to the vibration amplitude variation in a pump with a vibration fault. Highlights: ESP vibration is experimentally analyzed under different operating conditions. A more accurate amplitude extraction method for signals with frequency variations. Fluid-temperature difference between intake–discharge influences vibration. ESP vibration behavior characteristics for differential diagnosis are demonstrated.